2021
DOI: 10.3390/ijerph18073443
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ACE Gene I/D Polymorphism on Cardiometabolic Risk, Maximal Fat Oxidation, Cardiorespiratory Fitness, Diet and Physical Activity in Young Adults

Abstract: There is controversy about the relationship between ACE I/D polymorphism and health. Seventy-four healthy adults (n = 28 women; 22.5 ± 4.2 years) participated in this cross-sectional study aimed at determining the influence of ACE I/D polymorphism, ascertained by polymerase chain reaction, on cardiometabolic risk (i.e., waist circumference, body fat, blood pressure (BP), glucose, triglycerides, and inflammatory markers), maximal fat oxidation (MFO), cardiorespiratory fitness (maximal oxygen uptake), physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
(47 reference statements)
1
15
0
2
Order By: Relevance
“…Further studies need to analyze whether body fat percentage is associated with circulating free fatty acids levels, muscular fatty acid uptake, mitochondrial fatty acid transport and intramuscular triglyceride hydrolysis and oxidation. In addition, future studies should determine whether Metflex and body fat percentage are related with the genotype of the ADRB3, CD36 and ACE genes and the muscle content of CPT and ATGL which have been associated with MFO [ 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies need to analyze whether body fat percentage is associated with circulating free fatty acids levels, muscular fatty acid uptake, mitochondrial fatty acid transport and intramuscular triglyceride hydrolysis and oxidation. In addition, future studies should determine whether Metflex and body fat percentage are related with the genotype of the ADRB3, CD36 and ACE genes and the muscle content of CPT and ATGL which have been associated with MFO [ 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The search string results had an output of 29,092 articles and from these, 101 articles were identified as potential studies. After the full-text screening, 27 articles were excluded for the following reasons: six studies were not based on LACP (35)(36)(37)(38)(39)(40), five studies aimed to identify the effect of genomic ancestry (41)(42)(43)(44)(45), six studies focused only on genetic associations (46)(47)(48)(49)(50)(51), eight studies did not include cardiometabolic diseases (52)(53)(54)(55)(56)(57)(58)(59), and two studies investigated gene x phenotype interactions (60,61) as shown in Figure 5. Finally, after excluding the irrelevant articles based on the exclusion criteria, 74 studies were included in this systematic review as shown in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Heart rate and blood pressure Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured, after 10 min of sitting rest, by using an Omron M3 digital monitor (HEM-7051-E, Kyoto, Japan) as previously described (Montes-de-Oca-García et al, 2021). Heart rate was recorded at resting and during the exercise tests by using a Polar Team 2 monitoring equipment (Polar Electro Inc., Lake Success, NY, United States).…”
Section: Dietary Assessmentmentioning
confidence: 99%